ITC SOLUTIONS TO ACHIEVE PERFORMANCE AND EFFICIENCY OF HEALTH SERVICES: ONLINE VIRTUAL CLINIC - Adina BĂLAN (Management & Marketing)
The digital era modified the way people work, how the information and the informational resources are defined and organized. The organization which holds, uses and correctly reproduces the piece of information, the knowledge, the intellectual capital, becomes a leader in the proper field of activity. Following the actual tendencies in the digital era connected to the exchange of professional information, I can say that the exchange and sharing of digital information in a global multitude of interconnected computers are essential instruments that can contribute to the development and consolidation of the intellectual potential of the organization. This is why, the access of the individuals to information is an actual requirement of the development of the Romanian society in the context of globalization and world implication o contemporary processes and phenomena. The Digital integration eliminates the barriers that traditionally suppress the circuit of the medical information, lets the goods and services circulate to and from Romania by promoting efficiency as final purpose. Performance is needed in the health system, the transformation of the system of medical services by bringing the benefits of the medical science and technology to all individuals from every community. In order to accomplish these expectations it is needed that all the components that form the health system look at it as a whole and subscribe to modern solutions for improvement so that the quality of health should raise to an unprecedented level. Even if health systems differ from country to country from the organizational and financial point of view, they face the same challenges and problems, respectively the supply of medical care of better quality and keeping under control the health expenses. The use of information and communication technology in the field of medical assistance in order to stock, share, transmit and analyze clinical data and knowledge is more necessary than ever.